Effect of fibrous diets on feeding pattern, digestibility and physiological reactions in cattle and buffalo - BHATIA, S K; PRADHAN, K; SANGWAN, D C; SINGH, SADHANA; SAGAR, VIDYA (The Indian Journal of Animal Sciences, 2013)
The relative feed intake pattern, nutrient digestion and other related physiological parameters wen: studied in young male cattle (193 kg) and buffaloes (196 kg) by feeding wheat straw-groundnut-cake diet (9-10% CP) and sole berseem hay (11.5% CP), Buffaloes ate relatively less (p